UTILIZATION OF SUPPLY CHAIN MANAGEMENT FOR COMPANY COMPETITIVE ADVANTAGE - Suwanda, Suwanda (INFOKUM, 2022)
Utilization of Supply Chain Management (MRP) has become a crucial strategy in increasing a company's competitive advantage in the era of globalization and increasingly fierce competition. This research digs deeper into how companies can utilize MRP effectively to achieve and maintain competitive advantage. This research uses a qualitative approach with descriptive methods. The research results show that the implementation of Supply Chain Management (SCM) has a significant positive impact on the company. Through effective supply chain management, companies can increase customer satisfaction, optimize production and distribution costs, and achieve targeted financial goals. Utilization of technology in SCM supports improved employee performance and ensures good involvement in the supply chain process. Apart from that, SCM not only acts as a logistics tool, but also as an effective marketing strategy to respond to market needs and build close relationships with consumers. Overall, the implementation of SCM provides opportunities for companies to grow sustainably and gain competitive advantage in a dynamic market.